2011
DOI: 10.1371/journal.pone.0021682
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Action of the Mitochondria-Targeted Antioxidant SkQ1 on Retinopathy in OXYS Rats Linked with Improvement of VEGF and PEDF Gene Expression

Abstract: The incidence of age-related macular degeneration (AMD), the main cause of blindness in older patients in the developed countries, is increasing with the ageing population. At present there is no effective treatment for the prevailing geographic atrophy, dry AMD, whereas antiangiogenic therapies successful used in managing the wet form of AMD. Recently we showed that mitochondria-targeted antioxidant plastoquinonyl-decyl-triphenylphosphonium (SkQ1) is able to prevent the development and moreover caused regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 25 publications
(45 reference statements)
2
28
0
Order By: Relevance
“…In the present study, in support of our previous reports, [10][11]21 we demonstrated that dietary supplementation with the mitochondria-targeted antioxidant SkQ1 is effective at suppressing the development of retinopathy in OXYS rats. Here we for the first time showed that the therapeutic action of SkQ1 involves restoration (increase) of expression of a small heat shock protein, aB-crystallin, in the retina of OXYS rats.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, in support of our previous reports, [10][11]21 we demonstrated that dietary supplementation with the mitochondria-targeted antioxidant SkQ1 is effective at suppressing the development of retinopathy in OXYS rats. Here we for the first time showed that the therapeutic action of SkQ1 involves restoration (increase) of expression of a small heat shock protein, aB-crystallin, in the retina of OXYS rats.…”
Section: Discussionsupporting
confidence: 92%
“…35 It is thought that the accelerated senescence and development of age-related diseases in OXYS rats is also linked with progressive mitochondrial dysfunction. 21,23,36 Thus, we can hypothesize that SkQ1 protects against stress and restores mitochondrial function in the retina of OXYS rats. In RPE cells, aB-crystallin provides critical protection of mitochondrial function, which prevents ER stress-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…At present, we have the 102nd generation of OXYS rats with spontaneously developing cataract and accelerated senescence syndrome, which is characterized by early development of a phenotype similar to human geriatric disorders. This pathological phenotype primarily includes accelerated thymus involution, [28][29][30] retinopathy similar to human AMD, [31][32][33][34] high blood pressure, 35 and senile osteoporosis. 36-38 Accelerated brain aging manifests itself in OXYS rats as early development of behavioral and cognitive alterations against the background of neurodegenerative changes driven by an AD-like metabolic pathway.…”
Section: Introductionmentioning
confidence: 99%